UPAYA MENINGKATKAN BUDAYA KESELAMATAN PASIEN DI PUSKESMAS - Yudhanoorsanti Elmonita; Luky Dwiantoro; Agus Santoso (LPPM STIKES Muhammadiyah Kendal, 2022)
Patient safety concerns can help minimize the risk of KTD, reduce the occurrence of medical disputes, reduce conflicts between health workers and patients, reduce the lawsuits process, and dismiss allegations of malpractice which is increasing lately. The achievement of a good patient culture is done by building an understanding of the norms, beliefs, attitudes, and values that are important to nursing organizations. The systematic review of this study is aimed at identifying patient safety measures implemented by different countries to look at the effectiveness of patient safety culture in primary health care in global coverage. This research uses systematic review methods. Searching for journals was conducted in three well-known journals such as Proquest, ScienceDirect, and Scopus in the 2015-2021 publishing year. The term used is patient safety in the primary health care area and the community, as well as efforts made. Research on the database identified 7,967 articles to be filtered. After sorting and verifying the paper, data was taken from 12 papers explaining the culture of patient safety in primary health care. The articles taken have global coverage with research originating in several countries namely; Manchester, Sweden, Yemen, Lebanon, Germany, and Brazil. Characteristics of the study are grouped into the following themes: Patient safety in primary health care, and patient safety events in primary health care, Measurement of patient safety in primary health care, and Methods/ efforts to improve patient safety in primary health care. Tools that are used to measure patient safety, in general, are SAQ (Safety Attitudes Questionnaire), MOSPC (Medical Office Survey on Patient Safety Culture), and SOPS(Survey on Patient Safety Culture). This systematic review shows that many measurements can be taken to identify patient safety culture applications. Several efforts can be made to improve patient safety application, one of the important efforts in improving patient safety is improving knowledge. Education is an important step for the best patient safety intervention efforts. One of the programs that can be useful for the development of patient safety is the CUSP (Comprehensive Unit-based Safety Program) program.